INTEGRATION OF SHARIA ECONOMICS IN DEVELOPMENT ECONOMICS: AN ANALYSIS OF ITS ROLE AND POTENTIAL IN THE DIGITAL ERA - Syarifuddin, Syarifuddin (Economics Studies and Banking Journal (DEMAND), 2025)
This research analyzes the integration of the Islamic economy in the framework of modern development economics with a focus on the role  of Islamic fintech, Islamic financial instruments, and their impact on sustainable economic growth. Through secondary data analysis and a comprehensive literature review from the Scopus Q1 indexed journal, this study found that sharia economics contributes significantly to financial inclusion and equitable economic development. The results of the analysis show that the integration of sharia principles in the economic system can increase financial stability by up to 23% and expand financial access for the previously unbanked 40% of the population. Research recommends strengthening regulations, human resource development, and product innovation as the main strategies in optimizing the role of the Islamic economy in national development.